Treatment of Resistant Depression: A Pilot Study Assessing the Efficacy of a tDCS-Mindfulness Program Compared With a tDCS-Relaxation Program - Monnart, Aurore; Vanderhasselt, Marie-Anne; Schroder, Elisa; Campanella, Salvatore; Fontaine, Philippe; Kornreich, Charles (Frontiers in Psychiatry, 2019)
Background: This pilot study explores a therapeutic setting combining tDCS and Mindfulness-Based Cognitive Therapy for patients with drug resistant depression. tDCS has shown efficacy for depression treatment and improvement could be maintained with the combination with mindfulness, which has shown depression relapse prevention properties. Methods: 31 treatment-resistant depressed patients have been assigned to our experimental treatment-condition [tDCS combined with MBCT (n=15)] or to a control condition [tDCS combined with relaxation (n=16)]. Patients have completed both an intensive treatment block (8 consecutive days) and a single remind session two weeks after the intensive treatment. Clinical (depression, anxiety and rumination) and cognitive (general cognitive functioning, mental flexibility, working memory) symptoms of depression have been assessed through different questionnaires at baseline (t0), after the first block of treatment (t1), and after the remind session (t2). Results: Results seem to indicate a positive impact of both treatment-conditions on clinical and cognitive symptoms of depression at t1. However, the treatment condition combining tDCS with mindfulness has been found to better maintain clinical improvements at t2 regarding some clinical (MADRS and SARI) and cognitive variables (DIGIT SPAN-F and DIGIT SPAN-B). Conclusion: Based on the current observations, a multi-disciplinary treatment approach combining tDCS and Mindfulness-Based Cognitive Therapy might be effective in resistant depressed patients in the long run, even though further clinical research is necessary.